The effect of inflation and gross domestic product on value-added tax revenue in Indonesia with human development index as a moderating variable - Andini, Kanidia; Wijaya, Suparna (WIM Solusi Prima, 2024)
This research is a quantitative study aimed at examining the effect of inflation and Gross Domestic Product (GDP) on Value Added Tax (VAT) revenue in Indonesia, with the Human Development Index (HDI) as a moderating variable. The study utilizes secondary data obtained from the Central Bureau of Statistics, the World Bank, and the Central Government Financial Reports. The population includes data on inflation, GDP, HDI, and VAT revenue in Indonesia from the period of 1990 to 2022. Using a saturated sampling technique, a total of 33 samples were analyzed. The research employs time series data with an observation period from 1990 to 2022. The analytical method used is Moderated Regression Analysis (MRA), supported by the SPSS 23 software. The results of the analysis indicate that inflation negatively affects VAT revenue, while GDP positively influences VAT revenue. On the other hand, HDI does not moderate or significantly affect the relationship between inflation and VAT revenue or between GDP and VAT revenue. HDI, as a moderating variable, weakens the effect of inflation on VAT revenue because a higher HDI reflects a population with better education and income levels, which tend to maintain more stable consumption patterns despite inflationary pressures. HDI focuses on social aspects (education, health, and income) that do not directly influence the relationship between GDP and VAT revenue, as VAT revenue is predominantly driven by consumption.